Economy of plenitude – Polish reception of Clifford Douglas’s idea of social credit (Economic and Political Thought, 2014)
The aim of this text is to present Polish non-academic economic theoriesinspired by the concept of ‘social credit’ developed by Clifford Hugh Douglas.The focus of the current analysis is not only the theories as such, but alsosocial conditions for their emergence, construction and functioning. Mostof the ideas for reconstructing the financial and social system come froma community close to the foundation called We are Change. The essentialelement of the presented concepts is the idea of basic income, also calleda ‘social/national dividend’.